1979
DOI: 10.1016/0035-9203(79)90005-1
|View full text |Cite
|
Sign up to set email alerts
|

The Rift Valley fever epizootic in Egypt 1977–1978 2. Ecological and entomological studies

Abstract: Epidemiological factors related to the introduction, spread and maintenance of Rift Valley fever (RVF) virus were studied during the 1977-78 epizootic in Egypt, Culex pipiens is the most ubiquitous and prevalent mosquito species in the Nile Valley and Delta. Isolation of RVF virus from unengorged C. pipiens, and demonstration of laboratory transmission of the virus by this species, strongly implicate it as the chief vector in Egypt. Virus transmission to man also occurs by contamination when handling infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
112
1
4

Year Published

1985
1985
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(118 citation statements)
references
References 5 publications
1
112
1
4
Order By: Relevance
“…They associated this finding with the previous widespread abortions in camel herds which had instigated their investigations. Antibody to RVF in camel sera has also been reported from the sub-Saharan region of Nigeria (Fagbami, Tomori & Kemp, 1973) and more recently from Egypt (Ali & Kamel, 1978;Hoogstraal et al 1979) where RVF virus was also isolated from a camel (Imam, Karamany & Darwish, 1978) and the Sudan (Eisa, 1981).…”
mentioning
confidence: 78%
“…They associated this finding with the previous widespread abortions in camel herds which had instigated their investigations. Antibody to RVF in camel sera has also been reported from the sub-Saharan region of Nigeria (Fagbami, Tomori & Kemp, 1973) and more recently from Egypt (Ali & Kamel, 1978;Hoogstraal et al 1979) where RVF virus was also isolated from a camel (Imam, Karamany & Darwish, 1978) and the Sudan (Eisa, 1981).…”
mentioning
confidence: 78%
“…The disease is not considered to be contagious, and livestock generally acquire infection from transmission by arthropod vectors. In contrast, humans commonly become infected from contact with blood or other tissues of infected animals, but on occasion there appears to have been aerosol or droplet infection via mucosal surfaces, a phenomenon which has been demonstrated experimentally and which renders RVFV a candidate for use as a bioweapon [4,17,[35][36][37][38]. Hence, the apparent ability of SIN-based replicon vaccine to protect against intranasal RVFV challenge could be an important advantage.…”
Section: Discussionmentioning
confidence: 99%
“…12 African buffalo ( Syncerus caffer ) and Asian water buffalo ( Bubalus bubalis ) have been found to have high RVFV seroprevalence in other cross-sectional surveillance studies in Africa, and it has been suggested that they may serve as one of the amplifying hosts for RVFV. 13,14 Published reports also document that buffalo experience significant morbidity (fetal loss) from wild-type RVFV infections, and RVFV has been isolated from a water buffalo ( Bubalus bubalis ) fetus. 14,15 The objectives of this study were to identify whether lowlevel RVFV transmission is ongoing in African Buffalo ( Syncerus caffer caffer ) in Kruger National Park, South Africa, to examine the variation in buffalo RVFV seroprevalence over time, and to re-examine the potential contribution of infected buffalo to local RVFV transmission during and in between periods of known epizootics.…”
Section: Introductionmentioning
confidence: 99%